Effect of intraductal drug delivery of orexin receptor antagonists into rat mammary gland on milk triacylglycerol level: Possible molecular interaction with Gpat1 and Gpat4 genes: Orexin receptor antagonists change milk TAG level - Jafari Zandieh, Shima; Khazali, Homayoun (Iranian Journal of Pharmaceutical Sciences, 2022)
Although previous studies have demonstrated the importance of the orexin system in regulating enzymes involved in lipogenesis, its exact mechanism and the extent of this effect on different enzymes have remained unexplored. In this regard, this study is aimed at investigating the intra-duct injection of orexin receptor 1 and 2 antagonists (OX1RA and OX2RA) into the mammary glands. More specifically, the study probes the effect of this injection on glycerol 3-phosphate acyl transferase (Gpat1 and Gpat4) genes as well as the milk’s triacylglycerol (TAG) level in lactating Wistar rats. Twenty four lactating Wistar rats were randomly divided into different experimental groups including the control group, the group receiving OX1RA and OX2RA intraductally (at doses of 5, 10, and 20 µg/kg of B.W.). Six hours after injection, the collection of milk samples were done using rat milking device, and TAG measurements were carried out. Moreover, using real time PCR, we measured target genes by a specific primer for each gene. One-way ANOVA with Tukey’s post hoc tests were used to analyze the results and the level of significance was considered P<0.05. The findings of the present study showed that the injection of orexin antagonists at a dose of 10 μg/kg resulted in a significant reduction in Gpat1 and Gpat4 gene expressions. In addition, the injection of antagonists with the same dose caused a significant decrease in TAG levels. Intra-ductal injection of orexin antagonists into the mammary gland decreases milk TAG levels and decreases the expression of Gpat1 and Gpat4 genes.